Asuhan Keperawatan pada Pasien Stroke Hemoragik di Rumah Sakit Otak Dr. M. Hatta 2024 - Iweni Okma Sabma; Aini Yusra; Yulvi Hardoni (CV CENDIKIA JENIUS INDONESIA, 2026)
Hemorrhagic stroke is a medical emergency caused by the rupture of a blood vessel in the brain, potentially leading to severe neurological impairment and death. Increased intracranial pressure (ICP), decreased consciousness, motor dysfunction, and communication disorders are common clinical issues. This study aimed to implement nursing care for a hemorrhagic stroke patient at Dr. Drs. M. Hatta Brain Hospital, Bukittinggi, in 2024. The research method used a descriptive case study approach involving nursing care processes, including assessment, diagnosis, intervention, implementation, and evaluation over five days of treatment on one hemorrhagic stroke patient. Data collection techniques included observation, interviews, and direct measurement. Results showed the patient experienced right-sided hemiparesis, difficulty swallowing, headaches, and impaired verbal communication. The nursing diagnoses established were decreased intracranial adaptive capacity, impaired verbal communication, and impaired physical mobility. Nursing interventions provided included range of motion (ROM) exercises, ICP monitoring, and muscle strengthening. Evaluation indicated improvement in mobility function, cerebral perfusion, and verbal communication. In conclusion, appropriate and structured nursing interventions can accelerate recovery in hemorrhagic stroke patients. Nurses are advised to conduct comprehensive assessments and appropriate implementation to prevent complications and recurrent attacks.